Global methylation of blood leukocyte DNA and risk of melanoma. Issue 7 (6th January 2017) - Shen, Jie; Song, Renduo; Wan, Jie; Huff, Chad; Fang, Shenying; Lee, Jeffrey E.; Zhao, Hua
Abstract : Global DNA methylation, possibly influenced by lifestyle and environmental factors, has been suggested to play an active role in carcinogenesis. However, its role in melanoma has rarely been explored. The aims of this study were to evaluate the relationship between melanoma risk and levels of 5‐methylcytosine (5‐mC), a marker for global DNA methylation, in blood leukocyte DNA, and to determine whether this 5‐mC level is influenced by pigmentation and sun exposure. This case‐control study included 540 melanoma cases and 540 healthy controls. Overall, melanoma cases had significantly lower levels of 5‐mC% than healthy controls (median: 3.24 vs . 3.91, p  < 0.001). The significant difference between two groups did not differ by pigmentation or sun exposure. Among healthy controls, however, those who had fair skin color ( p  = 0.041) or light or no tanning after prolonged sun exposure ( p  = 0.031) or used a sunlamp ( p  = 0.028) had lower levels of 5‐mC% than their counterparts. In addition, those with an intermediate or high phenotypic index, an indicator of cutaneous cancer susceptibility, had 2.58‐fold greater likelihood of having a low level of 5‐mC% [odds ratio (OR): 2.58; 95% confidence interval (CI): 1.72, 3.96] than those with a low phenotypic index. Lower levels of 5‐mC% were associated with a 1.25‐fold greater risk of melanoma (OR: 1.25; 95% CI: 1.08, 1.37). A significant dose‐response relationship was observed in quartile analysis ( p  = 0.001). Our results suggest that global hypomethylation in blood leukocyte DNA is associated with increased risk of melanoma and that the level of methylation is influenced by pigmentation and sun exposure. Abstract : What's new? Factors that incite global losses in DNA methylation, which significantly impact genome integrity, are not well understood. An exception is in melanoma, where lifestyle and environmental factors, including sun exposure, are known to influence methylation. This study shows that levels of 5‐methylcytosine (5‐mC), a global methylation marker, is significantly reduced in melanoma patients and in healthy individuals with intermediate or high cutaneous phenotype index scores, which are indicative of fair, sun‐sensitive phenotypes. Reduced 5‐mC% levels were further linked to increased melanoma risk. The findings shed light on a molecular link between melanoma risk, methylation, and pigmentation and sun exposure.